THE INFLUENCE OF TECHNOLOGY-BASED LEARNING MEDIA AND VOCABULARY MASTERY TOWARD ENGLISH SPEAKING SKILL (EXPERIMENT AT VOCATIONAL SCHOOLS IN MAJALENGKA) - Komaida, Dian; Sumaryoto, Sumaryoto; Wulansari, Lusiana (Universitas Indraprasta PGRI, 2024)
The purpose of this study is to ascertain the following: 1) the influence of vocabulary mastery on English speaking ability; 2) the influence of learning media on English speaking ability; and 3) the combined effect of vocabulary mastery and learning media on the English speaking ability of Majalengka State Vocational School students. The experimental method is the one employed in this study. The 859 participants in this study were divided into 221 class XI students from SMK Negeri 1 Kertajati and 638 class XI students from SMK Negeri 1 Leuwimunding. Additionally, 120 students in total were used as research samples from the population. There were sixty pupils in the experimental class and sixty in the control class that made up the research sample. Following the instruction of Edpuzle and YouTube learning materials for the experimental group and Edpuzle learning materials for the control group, the following results are shown: 1) learning media significantly affects the capacity to speak English, as demonstrated by a sig value of 0.000 F count 17, 046. 2) Vocabulary expertise has a substantial impact on one's ability to speak English, as demonstrated by the sig value -0.000 < 0.05 and F count 15.779.